ANALYSIS OF STUDENTS"™ ERRORS WITH NEWMAN'S ERROR ANALYSIS ON VIBRATION, WAVES AND SOUNDS CONCEPT - Nurlaeli, Prita Dwi; Widiyatmoko, Arif (Jurnal Pendidikan Matematika dan IPA, 2023)
This study aims to find out what errors were made by Class VIII Junior High School students in story problem solving vibration, wave, and sound based on Newman's Error Analysis (NEA). And find out what factors are the cause of the error. This research is a qualitative research with a descriptive aroach. The data collection technique used is by using written tests, interviews, observations, and documentation. Then analyze the data using data reduction, data presentation, and verification. The results of this study indicated that Newman's Error Analysis can find out what mistakes were made by students and how these errors could occur. As for question number one, the percentage of reading errors is 0%, comprehension error is 14.28%, transformation error is 28.57%, process skills error is 19.04%, and encoding error is 0%. For question number two, the percentage of reading errors is 0%, comprehension error is 14.28%, transformation error is 19.04%, process skills error is 28.57%, and encoding error is 0%. Question number three type of reading error is 4.76%, comprehension error is 23.80%, transformation error is 9.52%, process skills error is 23.80%, and encoding error is 0%. Question number four reading error 0%, comprehension error 33.33% transformation error 19.04%, process skills error and encoding error is 0%. Question number five obtained 0% reading error, 33.33% comprehension error, 4.76% transformation and process skills, and 0% encoding error. This study concludes that many students experience errors because students don't understand the concept of the problem and are less thorough in working on the problem. From this it could be used as an evaluation for both students and teachers to be improving the learning process to make it more effective.